"It meant you were in trouble:" White teachers, race, and White shame. Issue 2 (3rd July 2019) - Crowley, Ryan M.
ABSTRACT: The author relates and develops Thandeka's notion of White shame to demonstrate how White teachers' early experiences with race can inhibit White racial identity development and work against racial justice. Through stories in which their interest in race or racial others was discouraged by people in the White community or in which inquiries they made about race were met with rebukes or silence, these teachers demonstrate the tacit, disjointed nature of White racial learning. The author uses the examples of White shame to encourage teacher educators to explore early memories of race and racial socialization as a way to help White pre-service teachers develop critical racial knowledge. The author suggests a racial pedagogy that connects the structural and personal elements of race, focuses on White complicity rather than White privilege, and encourages teachers to capitalise on teachable racial moments in the classroom.